2009
DOI: 10.1183/09031936.00025509
|View full text |Cite
|
Sign up to set email alerts
|

Muscle dysfunction and exercise limitation in adolescent idiopathic scoliosis

Abstract: Adolescent idiopathic scoliosis (AIS) can lead to ventilatory restriction, respiratory muscle weakness and exercise limitation. However, both the causes and the extent of muscle dysfunction remain unclear. The aim of our study is to describe muscle weakness and its relationship to lung function and tolerance to exercise in AIS patients.Lung and muscle function, together with exercise capacity, were assessed in 60 patients with pronounced spinal deformity (.40u) and in 25 healthy volunteers.Patients with AIS ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 55 publications
3
80
1
3
Order By: Relevance
“…In our study, we observed that AIS patients had a decrease in VO2, VO2kg, VE and VT when compared to the control group, as observed in previous studies that also used an incremental exercise protocol [11,12,20,22]. The peak of oxygen consumption is an important indicator of an individual's exercise capacity [23].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In our study, we observed that AIS patients had a decrease in VO2, VO2kg, VE and VT when compared to the control group, as observed in previous studies that also used an incremental exercise protocol [11,12,20,22]. The peak of oxygen consumption is an important indicator of an individual's exercise capacity [23].…”
Section: Discussionsupporting
confidence: 83%
“…As well, changes in the chest wall and spine are related to poorer performance during exercise. Other studies have compared the exercise capacity of AIS patients and non-affected individuals, however, they used the six-minute walk test [5] or cycle ergometer test [11,12,20]. Few studies used the ISWT to assess aerobic capacity in this population [21], but they did not assess the influence of the thoracic deformity on exercise variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, compared to healthy age-matched controls, a significant decrease in respiratory and limb muscle function was also observed in patients with adolescent idiopathic scoliosis that was associated with poorer exercise capacity, regardless of lung function 76 . Indeed, patients with adolescent idiopathic scoliosis exhibited significant alterations in body composition 77,78 .…”
Section: Scoliosismentioning
confidence: 80%
“…6 Studies on AIS prevalence have demonstrated that between 27% and 59% of patients suffer pain. 5,7 In addition, it may be associated with other conditions, such as restricted ventilation, respiratory muscle weakness, reduced quality of life, 8 and even psychological problems. 9 At present, according to the 2016 AIS consensus, 1 follow-up and management include observation, bracing or surgery.…”
Section: Introductionmentioning
confidence: 99%